Codes of conduct and codes of ethics as tools used to support the idea of social responsibility in supply chains - Rudnicka, Agata (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
Suppliers are important links in the value chain of modern enterprises. The rapid changes that are happening on the market now were an impulse for the development of concepts that help to manage such a complex environment. The concept of Corporate Social Responsibility (CSR) may support the development of sustainable supply chains. The management of social issues in supply chains is becoming more and more important. The main reasons for that is the increasing risk of undesirable situations in supply chains that can cause real problems for business. One of possible responds of business is the implementation of code of conduct or code of ethics addressed to suppliers. This paper presents the potential role of codes of ethics and codes of conduct as tools that support the management of social and environmental issues of supply chain. Theoretical considerations will be supported by a qualitative analysis of codes of ethics and codes of conduct published by socially responsible companies from Poland (on the basis on IX Ranking Odpowiedzialnych Firm)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 464, s. 91-100
Keywords: code of conduct; code of ethics; social responsibility in supply chain; qualitative analysis; kodeks postępowania; kodeks etyki; odpowiedzialność społeczna w łańcuchu dostaw; analiza jakościowa